Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content: 1. The Impact of Establishment King Abdullah University for Science and Technology on the Urban Growth in Thuwal Center in Jeddah Governorate Mrs. Aisha Abdulkareem Ataallah Bakhsh 2. The role of social media to promote a culture of values and sustainable development in the Asir region Adel Mohammed Abumalih 3. Cultural dialogue in the Islamic perspective and its role in achieving coexistence among civilizations Mrs. Shaymaa Nasser Hussain Al-Shammari 4. The stages of the play’s development from the ancient era to the Umayyad era Co-Prof. Narjees Abdulghaffar Saeed Bazuhair 5. The role of the Barbarossa brothers in extending the Ottoman influence in the central Maghreb (Algeria) (916-953 AH / 1510-1546 AD) Prof. Osama M. Abu Nahel 6. Cultural Approach to Literary Translation Dr. Mohamed Sidi Mohamed Sidi Mahmoud 7. The Use of Reporting Verbs in Arabic-English Social Science Articles: A Contrastive Corpus-based Analysis Dr. Jawharah SaeedAlasmari